2022
DOI: 10.3390/nu14153002
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Phytochemicals, Cellular Antioxidant Activities and Antiproliferative Activities of Raw and Roasted American Pistachios (Pistacia vera L.)

Abstract: The consumption of pistachios has been linked to many potential health benefits. Phytochemicals in pistachios, including phenolics, vitamin E and carotenoids, have been considered to make contributions to the health benefits. The objectives of this study were (1) to explore the phytochemical profiles (total phenolics and total flavonoids, including both free and bound forms), selected phytochemicals, vitamin E and carotenoids of raw and roasted pistachios; (2) to determine total antioxidant activity and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A previous review demonstrated that consumption of marine omega-3 poly-unsaturated fatty acids (PUFA) and fish may have a positive effect on cancer survival rates 36 . In addition, the unsaturated fatty acids, fiber, vitamins, minerals, and other compounds in nuts have been shown to have anticancer and antioxidant properties 37 . Patients should be advised to decrease their consumption of refined grains while increasing their consumption of whole grains, fish, shrimp, crab, and nuts.…”
Section: Discussionmentioning
confidence: 99%
“…A previous review demonstrated that consumption of marine omega-3 poly-unsaturated fatty acids (PUFA) and fish may have a positive effect on cancer survival rates 36 . In addition, the unsaturated fatty acids, fiber, vitamins, minerals, and other compounds in nuts have been shown to have anticancer and antioxidant properties 37 . Patients should be advised to decrease their consumption of refined grains while increasing their consumption of whole grains, fish, shrimp, crab, and nuts.…”
Section: Discussionmentioning
confidence: 99%
“…The carbohydrate content was measured by the phenol–sulfuric acid method with D-glucose as the standard [ 45 ]. The flavonoid content was measured using the sodium borohydride/chloranil method using catechin hydrate as a standard [ 46 ]. UA content was quantified by HPLC, using pure standards as reference for retention time and quantification [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gallic acid and other phenolic chemicals, such as phenol acids, flavonoids, stylibenes, and tannins, have one or more aromatic rings and hydroxyl groups [63][64][65]. As a great source of phenolic compounds, pistachios have strong antioxidant properties that can block ROS, preventing the oxidation of biological macromolecules [66]. The activity of the various pistachio nut components was evaluated in a number of in vitro and in vivo investigations, and the various lipophilic (carotenoids, tocopherols, and chlorophyll) and hydrophilic extracts were compared [67].…”
Section: Pistachiosmentioning
confidence: 99%
“…Additionally, it has been proposed that the antiproliferative properties of pistachios contribute to their anticancer properties. The growth of LT97 colon adenoma cells has been shown to be inhibited by pistachio fermentation supernatants in vitro in a dose-dependent manner [66]. Additionally, pistachio fermentation supernatants have been shown to increase antioxidant activity, which promotes the expression of catalase (CAT), which lessens DNA damage brought on by hydrogen peroxide (𝐻 2 𝑂 2 ) [70].…”
Section: Pistachiosmentioning
confidence: 99%